The Strategic Role of the Third Mission in Universities: A Concrete Case Study - Rosamaria Rusciano (European Scientific Journal, ESJ, 2024)
In addition to teaching and research, the goal of universities is to contribute to the development of civil society by promoting the direct application, valorization, and use of knowledge. In reality, it is a widespread and shared opinion that is no longer enough to carry out research on campus and publish subsequent works in scientific journals. It is also difficult to be fully satisfied with teaching only young people in university courses. This paper focuses on highlighting how an applied example can be taken as the best practice for future implementations. The methodology used is qualitative. The research question that initiated the study was to concretely verify how the Third Mission (TM) was integrated into the strategic choices of universities. In light of the new methods of evaluating universities, how can we highlight what they have done in terms of the third mission? Are organizational solutions possible in the approach to the TM? The objective was to verify what the impact and future development of the Third Mission (TM) in the universities will be. In light of its inclusion among the evaluation criteria of universities and teachers, the Third Mission (TM) is the new future frontier in terms of local and national openness and development, as well as their economic and financial sustainability. To this end, a case analysis was proposed as a model/best practice, and in particular the case of the Department of Business and Law of the University of Calabria was also presented. The application and implementation of rules and regulations are always difficult in any case and in any field. An example can be seen in public administration and universities, bureaucratically "plastered" and not very inclined to change and innovation, especially regarding performance evaluation. Therefore, seeing an application carried out relatively quickly allows the enhancement of the “DiScAG Model”, which is to be taken as an application example in the implementation of the Third Mission (TM) in universities. The study will contribute to increasing the literature and starting a discussion and a reflection on what has been done and what still needs to be done in this direction.